How can nitric oxide help osteogenesis? - Mônica H. M. Nascimento (AIMS Molecular Science, 2020)
Nitric oxide (NO) is endogenously produced free radical that plays important biological roles, such as, the promotion of vasodilation, angiogenesis, tissue repair, wound healing process, antioxidant, antitumoral and antimicrobial actions. Although the regenerative effects of NO in soft tissues have been extensively reported, its role in bone tissue repair has not been completely addressed. Both constitutive and inducible forms of NO synthase (NOS) are expressed in bone-derived cells, and some important cytokines, such as IL-1 and TNF, are potent stimulators of NO production. The effects of NO on bone tissue are dependent on its concentration. NO has dichotomous biological effects, at low concentrations (pico-nano molar range), NO may promote proliferation, differentiation and survival of osteoblasts, whereas at high concentrations (micromolar range) NO may inhibit bone resorption and formation. Therefore, at a certain concentration range, NO can avoid osteoclast-mediated bone resorption and promote osteoblast growth. Due to the potential beneficial effects of NO in bone tissue regeneration, the exogenous administration of NO might find important biomedical applications. As NO is a free radical and a gas, the administration of NO donors/generators has been explored in tissue repair. The delivery of NO to the bone using macromolecular NO releasing scaffolds has been shown to increase osteogenesis with a relevant impact in dental and orthopedist areas. In this sense, this review presents and discusses the recent and important progresses in the effects of NO/NO donors in bone tissue, and highlights the promising approach in the design and use of NO donors allied to biomaterials in the sustained and localized NO release for bone tissue regeneration.